CEO Power and ESG: The Moderating Role of Gender Diversity in Indonesia - Hesniati Hesniati; Madeline Natasha Arifin; Dewi Khornida Marheni; Tony Chandra (Jurnal Proaksi, 2025)
Main Purpose - The purpose of this study is to examine how CEO power influences ESG performance, taking into account board gender diversity. Method -  A total of 82 companies that issued sustainability reports in Indonesia between 2018 and 2022 were selected as the research subjects  and were analyzed using Ordinary Least Squares (OLS) regression.Main Findings -  The study shows that CEO Power contributes positively and significantly to ESG, and that the level of CEO power is related to the company's ESG performance. Although, gender diversity in the board is expected to strengthen inclusive governance and promote sustainability practices, in the context of Indonesian companies, this moderating influence has not yet been statistically observed. Theory and Practical Implications - This study extends upper echelons theory by showing that excessive CEO power weakens ESG performance, while board gender diversity serves as an effective internal governance mechanism to counterbalance such dominance. Novelty - Unlike prior studies that treat CEO power and board characteristics separately, this research introduces board gender diversity as a moderating mechanism that mitigates the negative impact of CEO power on ESG outcomes.